2014
DOI: 10.1111/ajr.12109
|View full text |Cite
|
Sign up to set email alerts
|

Mental health service use: Is there a difference between rural and non-rural women in service uptake?

Abstract: This study examines differences in uptake of the Medicare items rolled out in 2006 under the 'Better Access Scheme' (BAS) between rural and non-rural Australian women. It compares differences in women's uptake of the BAS services by area of residence (ARIA+) across time using the Australian Longitudinal Study of Women's Health (ALSWH) survey data linked to Medicare data. Women aged 28-33 years at the time the BAS was introduced that responded to the self-reported question on depression/anxiety and consented to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
21
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 35 publications
(48 reference statements)
4
21
1
1
Order By: Relevance
“…Moreover, people living in rural communities have limited access to health services and specialized services such as mental health services. Women living in rural areas with low education levels are less likely to seek care for mental illness compared to women living in urban areas (17) . From this perspective, we emphasize that several factors can influence the mental health of rural women.…”
mentioning
confidence: 96%
“…Moreover, people living in rural communities have limited access to health services and specialized services such as mental health services. Women living in rural areas with low education levels are less likely to seek care for mental illness compared to women living in urban areas (17) . From this perspective, we emphasize that several factors can influence the mental health of rural women.…”
mentioning
confidence: 96%
“…(24) Women living in rural areas and with a low educational level presented less inclination (in comparison with those living in urban areas) to seek care in face of a mental disorder, as they have limited access to health services, mainly specialized ones, such as mental disorder-related services. (25) The prevalence of mental disorders seems to be widely comparable in rural and urban areas, however there are differences between these two environments that may have different impacts and outcomes on the health of women. In general, living in a rural area limits access to health services and stigmatizes the public health within a cultural context.…”
Section: Discussionmentioning
confidence: 99%
“…The true extent of disadvantage faced by rural communities in comparison with their urban counterparts is difficult to ascertain [ 10 , 23 , 24 ], although the evidence is rising. The validity of the universal approach to mental illness in rural communities is questioned, as there is increasing evidence that there is “inequitable distribution of mental health care services across rural, remote and metropolitan areas” [ 25 ]. These discrepancies have been attributed to patient socioeconomic status, geographical location, and adequacy and availability of mental health services [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…These discrepancies have been attributed to patient socioeconomic status, geographical location, and adequacy and availability of mental health services [ 26 ]. Indeed, a recent study [ 25 ] demonstrated that a lower proportion of women in rural and regional areas accessed an Australian government-funded mental health initiative ‘Better Access’ Scheme compared to their non-rural counterparts, potentially reflecting a shortage of services or difficulty accessing them [ 25 ].…”
Section: Introductionmentioning
confidence: 99%